Viewing Geometry of the Mid-latitude Red Arcs and Aurora at the Station Vernadsky - Kravchenko, V. O.; Evtushevsky, O. M. (Ukrainian Antarctic Journal, 2005)
From the station Vernadsky the mid-latitude red arcs (SAR-arcs) can be observed low above the horizon toward the South Pole in the conditions of moderate geomagnetic activity and up to zenith during the magnetic storms. The mid-latitude aurora can appear in the region of the station during extreme magnetic disturbances. For the typical heights of SAR-arcs and aurora above Earth’ surface the interrelation between their possible angular heights above horizon and spatial distances and geomagnetic shells, which are covered by the optical observations of these objects from the stations is considered. Calculations show, that a line of sight is practically perpendicular to the geomagnetic field lines in the glow region in a wide interval of the distances. It gives an advantage in a study of the auroral emission height distribution.